FAMILY OWNERSHIP AND TAX AGGRESSIVENESS: MODERATE EFFECTS OF AUDIT QUALITY - Anggraini, Yety; Wismawati, Wahyu (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to analyze the effect of family ownership toward tax aggressiveness and the moderating effect of audit quality variables toward the relationship between family ownership and tax aggressiveness in manufacturing companies listed between the periods of 2013 – 2019. Sampling used purposive sampling method and obtained 55 family firm manufacturing with a period of 7 years of observation. Through several additional analyzes, the results of this study were quite varied. First, family ownership had a negative and significant effect on tax aggressiveness (H1 was accepted). Second, audit quality strengthened the negative effect of family ownership on tax aggressiveness (H2 was accepted). Third, testing of family versus non-family firms based on the dummy variable showed that it does not significantly affect tax aggressiveness. Fourth, testing of companies, especially ethnic Chinese, showed that there is no significant effect toward tax aggressiveness. Fifth, the examination of family companies on display showed that a significant effect toward tax aggressiveness. Sixth, testing of all estimation models with ETR (Effective Tax Rate) as an alternative measurement of BTD (Book Tax Differences) shows that there is a negative and no significant effect between family ownership and tax aggressiveness. Audit quality also does not significantly affect the moderate of family ownership relationships and tax aggressiveness, especially in the comparison of family and non-family firm, Chinese ethnic family firm, and multinational family firm. Keywords: Audit Quality, Chinese Ethnic, Family Ownership, Multinational Family Firm, Tax Aggressiveness.